Regional Variation in Restorative Treatment Need among Finnish Young People - Saujanya Karki; Antti Kämppi; Tarja Tanner; Jari Päkkilä; Marjo Seppänen; Leo Tjäderhane; Vuokko Anttonen; Pertti Patinen (Hindawi Limited, 2021)
Aim. To evaluate the regional variation in restorative treatment need among Finnish young people based on the socioeconomic factors. Materials and Methods. This cross-sectional study was conducted in 20 garrisons of the Finnish Defence Forces in January and July 2011. The study population comprised 13,819 Finnish conscripts born in the beginning of 1990s, including females. A computer-based survey was done together with clinical oral examination to gather background information, e.g., educational status. Furthermore, average annual income of the conscript's residence municipality was achieved from the Statistics of Finland. The zip code of the place of residence of each conscript was later extracted from the Mildoc® system. Georeferenced place of residence and income status were merged as information on provinces' level in a dataset. The association between the outcome variable and explanatory variables was determined by using the generalized linear mixed model, and geomaps were constructed. Results. Mean D value was 1.41 ranging from 0.89 (Kymenlaakso) to 2.33 (Kainuu). Higher education and high-income level were protective factors for restorative treatment need. Restorative treatment need was also low in those areas with high (OR: 0.70, 95% CI: 0.56-0.87) and medium (OR: 0.79, 95% CI: 0.70-0.89) yearly income compared to low yearly income. The high odds for the need of restorative treatment were discovered in Northern Ostrobothnia (OR: 2.26, 95% CI: 1.53-3.33) followed by Central Ostrobothnia (OR: 2.08, 95% CI: 1.17-3.70), Uusimaa (OR: 1.55, 95% CI: 1.16-2.08), and Central Finland (OR: 1.54, 95% CI: 1.10-2.16) compared to Varsinais-Suomi. Conclusion. In conclusion, there is a significant regional variation in restorative treatment need among Finnish young people in their twenties based on the socioeconomic factors.